McLintock! [videorecording (DVD)] - McLaglen, Andrew V. (Andrew Victor), 1920-2014; Wayne, John, 1907-1979; O'Hara, Maureen, 1920-2015; Wayne, Patrick, 1939- (John Wayne collection., 2005)
Cattle baron George Washington McLintock fights with his estranged wife who wants nothing from him except a divorce. His daughter and the local political land-grabbers are fighting with McLintock as well. Along with taming the West, McLintock finally "tames" everyone who has been fighting with him.